Sistem Informasi Rental Mobil Berbasis Website Menggunakan Metode Rapid Aplication Development (Studi Kasus : CV. Surya Rent Cars) - Reza Suryadi Gunawan; Muhtajuddin Danny; Suherman Suherman (DPPM Universitas Pelita Bangsa, 2022)
The business in the car rental sector in Indonesia has very promising prospects, because car transportation is the most popular type of transportation by the Indonesian people and the trend of car use continues to increase from year to year. Adapaun Surya Rent Car is a company engaged in car rental which in practice its business operational management activities still use the old method or manually. As in managing car data, rental transactions and making rental reports, company admins still use pens and paper, this often results in damage or loss of managed data. The method used in this study as a guide in designing a car rental information system using the Rapid Application Development method. This research is expected to minimize errors that often occur, speed up work time and provide convenience to company owners in managing company operational data at Surya Rent Cars. Keywords: Website, Car Rental, Information System, RAD